Identification of Multiple Drug-Resistance Genes in Clinical Isolates of Acinetobacter baumannii (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Around the world, Acinetobacter baumannii is a nosocomial pathogen that accounts for 80% of hospitalized patient infections. This opportunistic bacterium can cause a wide range of infections, including skin and soft tissue infections, meningitis, pneumonia acquired on a ventilator, urinary tract infections, and bacteremia, all of which have a high death rate of almost 63.3%. Finding multidrug-resistant genes in the clinical isolates of A. baumannii was the goal of this study. Twenty-four (24) A. baumannii clinical isolates were obtained from the Federal Teaching Hospital in Gombe, Nigeria, and subcultured on MacConkey agar for eighteen to twenty-four hours at 37 ˚C. The isolates were identified using traditional biochemical testing, morphology, and cultural traits. The VITEK was then used to validate the identification. Twenty of the 24 isolates had been identified as A. baumannii. The Kirby Bauer method and CLSI recommendations were utilized to determine the antibiotic susceptibility of the A. baumannii isolates. Polymerase Chain Reaction was used to identify the genes that were resistant to many drugs. According to the data, fifteen (15) A. baummanii isolates, or 75% of the total, were likely multidrug resistant. The presence of the BlaNDM-1 gene in eight isolates, the BlaOXA23 gene in six isolates, and the BlaVIM gene in just four isolates was confirmed by molecular detection of the MDR genes from these isolates. These results show that a significant portion of the isolates of A. baumannii carried genes resistant to many drugs, which could be the root cause of any infection treatment failure caused by this organism.
Keywords: Acinetobacter baumannii; Identification; Sensitivity test; Multidrug resistance; Polymerase Chain Reaction